Maggot metabolites and their combinatory effects with antibiotic on Staphylococcus aureus - Lim Chu; Baptista Carl; Arora Shuchi (BMC, 2011)
Abstract Background Maggot therapy has been in practice for effective debridement, disinfection and healing of chronic wounds. Due to their antiseptic action during wound healing, their metabolites have been investigated in the past for antibacterial activity. They have been particularly useful for treatment of wounds infected with multi-drug resistant Staphylococcus aureus. Antibiotics, on the other hand, can predispose bacteria to develop resistance. Substances that are able to modulate or delay the occurrence of resistance in bacteria are under investigation by many researchers around the world. In the present study, antibacterial activity in excretions/secretions (ES) from maggots of Lucilia cuprina blowfly was demonstrated. The extracts were also screened in combination with antibiotic, ciprofloxacin. Methods L. cuprina blowfly maggots were reared for extraction of its metabolites. The ES extracted was screened against S. aureus, alone and in combination with ciprofloxacin, both for short term and long term exposure analysis. A microchannel-based device and system was used for experiments instead of conventional techniques. Results The original ES had shown partial bacterial growth inhibition. However, in combination with ciprofloxacin, at sub-inhibitory concentrations, certain combinations revealed anti-staphylococcal activity, with bacterial reduction of up to 50%, after 24 hours. The six day study on S. aureus exposed to ES-ciprofloxacin combination suggested a potential delay in development of adaptive resistance as opposed to when ciprofloxacin was used as single agent. Conclusions The combination effect of ES and ciprofloxacin at sub-MIC levels showed enhanced antibacterial activity compared to the effect of ES and ciprofloxacin as single agents. Based on the results of ES-ciprofloxacin combinations, a more effective means of treatment for S. aureus can be proposed.